Acylation Modification of Antheraea pernyi Silk Fibroin Using Succinic Anhydride and Its Effects on Enzymatic Degradation Behavior - Xiufang Li; Ceng Zhang; Lingshuang Wang; Caili Ma; Weichao Yang; Mingzhong Li (Journal of Chemistry)
The degradation rate of tissue engineering scaffolds should match the regeneration rate of new tissues. Controlling the degradation behavior of silk fibroin is an important subject for silk-based tissue engineering scaffolds. In this study, Antheraea pernyi silk fibroin was successfully modified with succinic anhydride and then characterized by zeta potential, ninhydrin method, and FTIR. In vitro, three-dimensional scaffolds prepared with modified silk fibroin were incubated in collagenase IA solution for 18 days to evaluate the impact of acylation on the degradation behavior. The results demonstrated that the degradation rate of modified silk fibroin scaffolds was more rapid than unmodified ones. The content of the β-sheet structure in silk fibroin obviously decreased after acylation, resulting in a high degradation rate. Above all, the degradation behavior of silk fibroin scaffolds could be regulated by acylation to match the requirements of various tissues regeneration.